Synthesis of New 2, 4, 5-Triphenyl Imidazole Derivatives Derived from Benzoin and Studying their Biological Activity - Rana S. Ahmed (Journal of Global Pharma Technology, 2019)
In this work a series of new 2, 4, 5-triphenyl imidazole derivatives were synthesized. In the beginning, compound [1] was formed from the reaction of benzoin and benzaldehyde in the presence of ammonia, which was reacted with sodium hydride in DMF to obtain imidazole salt. This salt was reacted with adipoyl chloride to give compound [2]. Acid hydrazide derivative [3] was obtained from the reaction of compound [2] with hydrazine hydrate. After that Shiff bases [4-9] have been synthesized from the reaction of compound [3] with different aromatic aldehydes. These new formed compounds were diagnosed by 13C-NMR, 1H-NMR for some of them (in Ahl-Albate University in Jordan) and FT-IR spectroscopy (In Baghdad University). All of the prepared products have been studied their biological activities toward two kinds of bacteria. These products showed good efficacy to moderate toward bacteria.Keywords: Imidazole, Shiffs bases, Biological activity.